DEPRESSION IN A GROUP OF PATIENTS WITH CHRONIC RENAL FAILURE ATTENDING HEAMODIALYSIS UNIT IN TEACHING HOSPITAL IN BAGHDAD (Iraqi Journal of Medical Sciences, 2016)
Background:Depression is the most common psychopathological condition among patients with chronic renal disease yet it is still under recognized and underestimated. Depression adversely affects the already disturbed quality of life of patients with chronic renal disease.Objectives:To determine the rate of depression in a sample of chronic renal failure patients attending haemodialysis unit in teaching hospital in Baghdad and examine the sociodemographic variables of such patients.Methods:This is a cross-sectional study done at Al-Kadhmyia Teaching Hospital, during a period of 2 months from 4th of January 2009 to 4th of March 2009. The total of 50 random cases with chronic renal failure coming for haemodialysis were interviewed by semi structured schedule for psychiatric diagnosis. Results were reviewed by simple descriptive and inferential statistical measures.Results:The rate of depression in this sample of patients with chronic renal failure was 40%.There was no statistically significant relation between any of the demographic variables and depression.Conclusion:The rate of depression in this study is high. Results were compared with other studies in light of circumstances of this study.Key words:Depression, chronic renal failure, haemodialysis
Keywords: Depression; chronic renal failure; haemodialysis